Aplikasi Pendeteksi Citra yang diambil dari Kamera Mobile Device untuk Menghasilkan Ensiklopedia Fauna Berbasis Android - Joshua Caine Buwono; Liliana Liliana; Henry Novianus Palit (Jurnal Infra, 2017)
Finding new animals can sometimes be something new for humans. If both tame or wild animal is found, it usually search for information about the animal would do. However, knowledge of these animals still tend to be minimal. Questions arise about knowledge of these animal. However, this knowledge comes after the animal attacked. Therefore, the solution provided is an application that generates information that is always new with image detection technology. Thus, with just a photograph, information can be obtained easily and quickly. Application can be run on Android Jellybean operating system API 17 and so on.